Antihypercholesterolemic potential of bioactive compounds in Phaseolus vulgaris: A narrative review - Huriyah Tsabitah Rahmallah; Diniatik Diniatik; Asmiyenti Djiliasrin Djalil (Malahayati International Journal of Nursing and Health Science, 2026)
Background: Hypercholesterolemia is a metabolic disorder characterized by increased cholesterol levels, especially low-density lipoprotein (LDL), in the blood circulation. This condition contributes significantly to the incidence of coronary heart disease and stroke, and is a global public health burden. Standard therapy using lipid-lowering drugs such as statins has been proven effective, but is associated with adverse effects, such as myopathy, hepatotoxicity, and long-term treatment resistance. Therefore, the search for safer and more affordable natural therapeutic alternatives is important. One potential plant that is widely consumed and relatively safe is beans (Phaseolus vulgaris L.). Purpose: To narratively review scientific evidence related to the hypercholesterolemic activity of bioactive compounds in beans (Phaseolus vulgaris L.) based on in vitro and in vivo research results. Method: This narrative review involved a literature search conducted in three electronic databases: Google Scholar (n = 58), ScienceDirect (n = 11), and PubMed (n = 2), yielding a total of 71 articles. The search strategy employed Boolean operators using the following keywords: ("beans" AND "Phaseolus vulgaris L." AND "hypercholesterolemia" AND "bioactive compounds" AND "isolation") OR "fractionation". The inclusion criteria comprised original research articles published between 2015 and 2025, with full-text availability. Articles were excluded if they were duplicates, did not present primary research data, or had titles that were not relevant to the predefined search keywords. Results: Bioactive compounds in Phaseolus vulgaris L. work through multiple mechanisms, including inhibition of cholesterol synthesis, increased excretion, and protection against LDL oxidation. Phaseolus vulgaris demonstrates considerable therapeutic potential as a safe and effective herbal therapy in the management of hypercholesterolemia. Conclusion: Current preclinical evidence indicates that bioactive compounds in Phaseolus vulgaris may support cholesterol reduction through several complementary mechanisms. However, well-designed human clinical trials are required to confirm their efficacy and safety.